Family Support in a Study about Schoolchildren Facing Contexts of Vulnerability - Bazán Ramírez, Aldo (2021)
The relationship between families and their children´s school has been empirically addressed, theorized and characterized. A study aimed at analyzing actions and incentives tied to academic support received from families was conducted at the home of fifth grade students who faced medium level conditions of vulnerability. eight relatives of the group of students who were selected through intentional sampling. A content analysis of the information collected revealed the coincidences between the relatives of students with low and high performance: they execute reinforcement activities, are self-taught and have the time, resources and materials necessary for studying at home. The differences lie in expectations: high-performing students are supported with the intention that they achieve success in their studies and in their professional future. Students with a poor academic achievement receive support from their parent figures in the hope that they will not repeat their failure patterns and achieve a better quality of life. It is concluded that family support practices are influenced by personal history, expectations towards their descendants and beliefs about education.